Opening the Black Box of the Danish Dairy Cooperatives: A Productivity Analysis - Sofia Henriques; Eoin McLaughlin; Paul Sharp; Xanthi Tsoukli; Christian Veddel (European Historical Economics Society (EHES), 2020)
The rapid spread of the Danish dairy cooperatives from the 1880s until the First World War is often portrayed as a uniform wave which swept the country. We investigate this using exceptionally detailed micro-level panel data taken from the Operational Statistics of Creameries, which were published from 1898 until after the Second World War. Our database comprises 1419 creameries over the period 1898- 1945 and no less than 131 variables. We document the data, and use a simple fixed effects setup to demonstrate considerable heterogeneity in the productivity of the individual creameries both over time and across space. We conclude by suggesting reasons for this, including scale of production, accessibility of fuel, religious institutions, and more.
Keywords: N53; N54; Q13; 330; Creameries; Denmark; productivity